\[\boxed{\mathbf{751\ (751).\ }Еуроки\ - \ ДЗ\ без\ мороки}\]
\[a_{1} = y^{2} + 1,\ \ a_{2} = y^{2} + y,\ \ \]
\[a_{3} = 8y - 10.\ \ \]
\[Тогда:\ \ \ \ 2a_{2} = a_{1} + a_{3}\]
\[2 \cdot \left( y^{2} + y \right) = y^{2} + 1 + 8y - 10\]
\[2y^{2} + 2y = y^{2} + 8y - 9\]
\[y^{2} - 6y + 9 = 0\]
\[(y - 3)^{2} = 0\]
\[y = 3\]
\[a_{1} = 9 + 1 = 10,\]
\[\text{\ \ }a_{2} = 9 + 3 = 12,\ \ \]
\[a_{3} = 24 - 10 = 14.\ \]
\[Ответ:y = 3;\ a_{1} = 10,\ \]
\[a_{2} = 12,\ a_{3} = 14\text{.\ }\]
\[\boxed{\mathbf{751.\ }Еуроки\ - \ ДЗ\ без\ мороки}\]
\[В\ окружность\ R\ вписан\ ⊿,\ \]
\[тогда\ его\ сторона\ a_{1} =\]
\[= R\sqrt{3},\ P_{1} = 3a_{1} = 3R\sqrt{3},\]
\[S_{1} = \frac{a_{1}^{2} \cdot \sqrt{3}}{4} = \frac{\left( R\sqrt{3} \right)^{2} \cdot \sqrt{3}}{4} =\]
\[= \frac{R^{2} \cdot 3\sqrt{3}}{4};\ \ длина\ \]
\[окружности\ c_{1} = 2\pi R,\]
\[площадь\ круга\ S_{1}` = \pi R^{2}.\ В\ \]
\[треугольник\ вписана\ \]
\[окружность\ R_{2} = \frac{R}{2};\ \]
\[c_{2} = 2\pi\frac{R}{2} = \pi R;\ \ \]
\[S_{2}` = \pi \cdot \left( \frac{R}{2} \right)^{2} = \frac{\pi R^{2}}{2}.\]
\[В\ окружность\ R_{2}\text{\ \ }вписан\ \]
\[треугольник\ со\ стороной\]
\[\ a_{2} = \frac{R}{2} \cdot \sqrt{3},\]
\[\ P_{2} = 3a_{2} = \frac{3R\sqrt{3}}{2};\ \ \ S_{2} =\]
\[= \left( \frac{R\sqrt{3}}{2} \right)^{2} \cdot \frac{\sqrt{3}}{4} = \frac{R^{2} \cdot 3\sqrt{3}}{16}\text{\ \ }и\ \]
\[так\ далее.\]
\[1)\ 3R\sqrt{3},\frac{3R\sqrt{3}}{2},\ \frac{3R\sqrt{3}}{4},\ldots -\]
\[геометрическая\ прогрессия;\ \]
\[\text{\ \ }q = \frac{1}{2},\]
\[S = \frac{3R\sqrt{3}}{1 - \frac{1}{2}} = \frac{3R\sqrt{3}}{\frac{1}{2}} = 6R\sqrt{3};\]
\[2)\ \frac{R^{2}3\sqrt{3}}{4},\ \frac{R^{2}3\sqrt{3}}{16},\ \frac{R^{2}3\sqrt{3}}{64},\ldots -\]
\[геометрическая\ прогрессия;\ \ \ \]
\[q = \frac{1}{4},\]
\[S = \frac{R^{2}3\sqrt{3}}{4 \cdot \left( 1 - \frac{1}{4} \right)} = \frac{R^{2}3\sqrt{3}}{4 \cdot \frac{3}{4}} =\]
\[= \frac{R^{2}3\sqrt{3}}{3} = R^{2}\sqrt{3};\]
\[3)\ 2\pi R,\ \pi R,\frac{\text{πR}}{2},\ldots -\]
\[геометрическая\ прогрессия;\ \ \]
\[\ q = \frac{1}{2},\]
\[S = \frac{2\pi R}{1 - \frac{1}{2}} = \frac{2\pi R}{\frac{1}{2}} = 4\pi R;\]
\[4)\ \pi R^{2},\frac{\pi R^{2}}{4},\frac{\pi R^{2}}{16},\ \ldots -\]
\[геометрическая\ прогрессия;\]
\[\ \ q = \frac{1}{4},\]
\[S = \frac{\pi R^{2}}{1 - \frac{1}{4}} = \frac{\pi R^{2}}{\frac{3}{4}} = \frac{4\pi R^{2}}{3}.\]
\[Ответ:1)\ 6R\sqrt{3};\ 2)\ R²\sqrt{3};\ \ \]
\[3)\ 4\pi R;\ 4)\frac{4\pi R^{2}}{3}.\]